Povos indígenas no Espírito Santo: uma história de luta e resistência - Litig, Claudio Ernani (2016)
This research investigated the social, cultural and economic impacts suffered by indigenous nations in the state of Espírito Santo, because of the new demarcation and ratification of their land and the process of struggle and resistance that intend to redeem the collective rights of these people. The study was developed in third time: In the first time, the study analyzed the academic literature, lifting of indigenous historic informations, the implantation process of the industrial complex of COFAVI and Aracruz Cellulose and the process of demarcation and ratification of indigenous land. The second time investigated the governmental documents to evaluate environmental, social, cultural and economic impacts caused by the eucalyptus monoculture and the impacts at institutions and public services. The third time executed a field research, identifying and registering impacts resulted by eucalyptus monoculture and the impacts at institutions and public service with reflex on indigenous land. It was found damage for all extension of indigenous land. The research allowed conclude that, to recover the indigenous' collective rights it's necessary to pressure the government of Espírito Santo and the City Hall of Aracruz to evaluate the environmental, social, cultural and economic impacts caused by private companies and the public power itself